Unleashing the Barriers to CSR Implementation in the SME Sector of a Developing Economy: A Thematic Analysis Approach - Asif Mahmood (MDPI AG, 2021)
The notion of corporate social responsibility (CSR) from the perspective of sustainability has been a part of the academic discussion in recent years. Different studies have also highlighted the inability of the SME sector to implement a CSR plan to achieve sustainability objectives. However, why this sector is unable to adopt CSR is something that has not been properly attended by contemporary scholars. Against this backdrop, the current study aims to explore the major barriers that inhibit SMEs from implementing CSR and sustainability measures. The current study data were collected from the senior management of different SMEs in Pakistan and were analyzed using thematic analysis to extract different patterns of themes. The results unveil that the “lack of finances” is the most critical barrier for CSR, followed by the “lack of CSR knowledge.” The implications for theory and practice are also discussed in detail.